A Meta-Analysis of Observational Studies on the Association of Chronic Urticaria With Symptoms of Depression and Anxiety - Huang, Yuzhou; Xiao, Yi; Zhang, Xingyu; Li, Jie; Chen, Xiang; Shen, Minxue (Frontiers in Medicine, 2020)
Abstract Background: Chronic urticaria (CU) is a frequently occurring skin condition associated with many psychological factors, but the effect size of associations varied in literature. Objectives: To perform a systematic review and meta-analysis on the associations of CU with symptoms of depression and anxiety. Methods：Using a prespecified protocol, we systematically searched articles published in PubMed, Web of Science, CNKI and CQVIP databases between January 2000 and January 2019. Pooled estimates in terms of odds ratios (ORs) and standardized mean differences (SMDs) were calculated according to outcome measures. Subgroup analysis by disease subtypes and tool of measurement, and sensitivity analysis were performed. Risk of bias and quality of studies were evaluated. Results: Twelve studies were selected for systematic review. The ORs were 3.99 (95%CI: 3.24 to 4.91, P<0.001) for anxiety and 2.94 (95%CI: 2.42–3.58, P<0.001) for depression. The SMDs of severity were 0.98 for anxiety (95%CI: 0.76–1.200, P<0.001), and 0.84 for depression (95%CI: 0.59–1.10, P<0.001). Subgroup assessment by disease subtypes and tool of measurement showed variations in effect size, where chronic spontaneous urticaria showed greater effects on anxiety (OR=6.62, 95%CI: 3.67–11.95, P<0.001), and depression (OR=6.13, 95%CI: 2.31–16.31, P<0.001). Sensitivity analysis demonstrated consistent results. Conclusion: CU is associated with two- to three-fold risks of anxiety and depression.